Efficacy of denture cleansers on impact strength of heat polymerized acrylic resins - Mallikarjuna Ragher; Uma Mayoor Prabhu; Jaya Prakash Ittigi; Ravi Naik; C S Mahesh; M R Pradeep (Wolters Kluwer Medknow Publications, 2017)
Purpose: The study was aimed to compare and evaluate the changes in the impact strength of heat cure denture base resins when treated using denture cleansers. Methodology: Study was conducted with sample size of 40 and dimesion 65 mm length, 10 mm width, and 3 mm thickness as per the ISO 1567. Distilled water has been used as control group, in which 10 samples were immersed of 40 samples. Of remaining 30 samples, 10 were treated with Clinsodent, 10 were treated with VI-Clean, and 10 were treated with Clanden denture cleansers. The impact strength of these specimens from each group was tested with the help of Charpy-type pendulum impact strength tester. The energy absorbed to fracture the specimens was recorded, and impact strength was calculated and was analyzed using Kruskal-Wallis ANOVA and Mann-Whitney test. Results: Impact strength of samples was significantly reduced after immersion in denture cleansers Clinsodent, VI-Clean, and Clanden solutions when compared to control group. Conclusion: Clinsodent, VI-Clean, and Clanden denture cleansers decrease the impact strength of heat cure denture base resin after immersion. Hence, the study concludes that denture cleansers should be used with caution and advised to follow manufacturer's instructions.